Electrochemical study of composite materials for coal-based direct carbon fuel cell. (12th July 2018) - Ali, Amjad; Shehzad Bashir, Farrukh; Raza, Rizwan; Rafique, Asia; Kaleem Ullah, Muhammad; Alvi, Farah; Afzal, Muhammad; Ghauri, Moinuddin; Belova, Lyubov M.
Abstract: The efficient conversion of solid carbon fuels into energy by reducing the emission of harmful gases is important for clean environment. In this regards, direct carbon fuel cell (DCFC) is a system that converts solid carbon directly into electrical energy with high thermodynamic efficiency (100%), system efficiency of 80% and half emission of gases compared to conventional coal power plants. This can generate electricity from any carbonaceous fuel such as charcoal, carbon black, carbon fiber, graphite, lignite, bituminous coal and waste materials. In this paper, ternary carbonate-samarium doped ceria (LNK-SDC) electrolyte has been synthesized via co-precipitation technique, while LiNiCuZnFeO (LNCZFO) electrode has been prepared using solid state reaction method. Due to significant ionic conductivity of electrolyte LNK-SDC, it is used in DCFC. Three types of solid carbon (lignite, bituminous, sub-bituminous) are used as fuel to generate power. The X-ray diffraction confirmed the cubic crystalline structure of samarium doped ceria, whereas XRD pattern of LNCZFO showed its composite structure. The proximate and ultimate coal analysis showed that fuel (carbon) with higher carbon content and lower ash content was promising fuel for DCFC. The measured ionic conductivity of LNK-SDC is 0.0998 Scm −1 and electronic conductivity of LNCZFO is 10.1 Scm −1 at 700 °C, respectively. A maximum power density of 58 mWcm −2 is obtained using sub-bituminous fuel. Highlights: Li0.12 Ni0.32 Cu0.32 Zn0.12 Fe0.12 O3-δ electrode was developed for direct carbon fuel cell. Micro-structure, carbon content and carbon reactivity enhance the fuel cell performance. Reaction kinetic depends upon the direct oxidation of carbon particle at anode TPB. The measured conductivity of electrode was found to be 10.1 Scm −1 at 700 °C.